2021
DOI: 10.3390/cells10123305
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Anandamide Attenuates Acute Respiratory Distress Syndrome through Modulation of Microbiome in the Gut-Lung Axis

Abstract: Acute respiratory distress syndrome (ARDS) is a serious lung condition characterized by severe hypoxemia leading to limitations of oxygen needed for lung function. In this study, we investigated the effect of anandamide (AEA), an endogenous cannabinoid, on Staphylococcal enterotoxin B (SEB)-mediated ARDS in female mice. Single-cell RNA sequencing data showed that the lung epithelial cells from AEA-treated mice showed increased levels of antimicrobial peptides (AMPs) and tight junction proteins. MiSeq sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 87 publications
1
23
0
Order By: Relevance
“…4.7.3. The Relationship between Gut Microbiota, AEA, and Acute Respiratory Distress Syndrome AEA was found to attenuate acute respiratory distress syndrome through modulating the gut microbiota [420]. In this study, the researchers investigated the effect of AEA on staphylococcal enterotoxin B (SEB)-mediated acute respiratory distress syndrome.…”
Section: The Relationship Between Gut Microbiota the Endocannabinoid ...mentioning
confidence: 99%
See 3 more Smart Citations
“…4.7.3. The Relationship between Gut Microbiota, AEA, and Acute Respiratory Distress Syndrome AEA was found to attenuate acute respiratory distress syndrome through modulating the gut microbiota [420]. In this study, the researchers investigated the effect of AEA on staphylococcal enterotoxin B (SEB)-mediated acute respiratory distress syndrome.…”
Section: The Relationship Between Gut Microbiota the Endocannabinoid ...mentioning
confidence: 99%
“…In this study, the researchers investigated the effect of AEA on staphylococcal enterotoxin B (SEB)-mediated acute respiratory distress syndrome. SEB caused an increase in pathogenic bacteria in both the lungs and the gut [420]. AEAtreated mice showed increased level of anti-microbial peptides in the lung epithelial cells and prevented the increase in pathogenic bacteria induced by SEB [420].…”
Section: The Relationship Between Gut Microbiota the Endocannabinoid ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the imbalance of COPD microbiota is related to the increase of harmful bacteria and affect the production of SCFAs. The correlations between the intestinal and pulmonary microbiota add pieces of evidence to the GLA [53,[64][65].…”
Section: There Is a Significant Relationship Between Gut-lung Axis Mi...mentioning
confidence: 96%